The Iterative Development of an Online Multiplayer Escape Room Game for Improving Social Interaction through Edutainment - Najm, Ali; Christofi, Maria; Hadjipanayi, Christos; Kyrlitsias, Christos; Michael-Grigoriou, Despina (My University, 2022)
Digital Games are nowadays used for several purposes beyond entertainment. Such purposes include but are not limited to education, promoting cultural heritage, and improving well-being aspects. A rich body of literature presents experimental studies, investigating whether a serious game achieves its aim. However, most of such papers often omit to provide adequate information on the development process followed, game mechanisms and techniques used, making the reproducibility of the game as such, by other researchers, difficult. This results in a lack of knowledge transfer between researchers, who usually must develop applications under investigation by themselves when at the same time industrial gaming companies rarely publicize the technical insights of their work. This paper aims to contribute towards filling this knowledge gap within the scientific community, using as a case study an online, multiplayer, escape room game, which aims to improve social interaction through edutainment. The full process of its development with details for the various components that the game comprises are presented. We are expanding on the functionality of the game and the optimization of the 3D environment and the assets, among other aspects. Results of white and black-box testings taking place at the end of each development cycle showed that the integration of the various components described within the paper led to a robust game.
Keywords: Serious Games; Iterative Development; Edutainment; Multiplayer; Online; Social Interaction